THE ISSUES OF THE ACTIVATION OF HUMAN FACTORS (Scientific journal of the Fergana State University, 2023)
The article is devoted to the scientific multyplanned fastors of the human actions, the social factors, which influence on all the sphears of society, the pecularities and laws of manifestation in the society